Intention to Use Mobile Easy Payment Services: Focusing on the Risk Perception of COVID-19 - Kim, JiWon; Kim, Mincheol (Frontiers in Psychology, 2022)
Since the COVID-19 outbreak, the utilization rate of mobile easy payment services that minimize human contact has increased rapidly. Therefore, many studies have explored the relationship between the COVID-19 pandemic and the intention to use mobile easy payment services. These studies assume that the relationship between variables is simply linear. However, complex relationships between variables cannot be fully analyzed in a linear fashion as most relationships between variables in social phenomena are nonlinear. Therefore, this study attempted to analyze the nonlinear relationships between factors influencing the intention to use mobile easy payment services since the COVID-19 outbreak by applying the extended technology acceptance model (TAM2). Online and offline surveys were conducted with users who have used mobile easy payment services since the COVID-19 outbreak; 227 samples were secured for analysis. In addition, an empirical analysis was conducted using WarpPLS 7.0 software to determine the linearity of relationships between variables. The results showed that subjective norms, perceived ease of use, and perceived usefulness had significant effects on the intention to use mobile easy payment services. In addition, the COVID-19 pandemic had a significant moderating effect, implying nonlinear relationships between variables. Based on the results, this study proposes that the pandemic is a factor influencing the intention to use mobile easy payment services, and recommends that providers adopt marketing strategies, such as improving the usefulness of services.